2021
DOI: 10.1002/ajh.26290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Levitt's CO breath test and the 15N‐glycine labeling technique for measuring the lifespan of human red blood cells

Abstract: The red blood cell (RBC) lifespan is an important physiological indicator of clear significance in clinical research, used for the differential diagnosis of various diseases such as anemia, compensatory phase hemolysis, and polycythemia. The 15 N-glycine labeling technique is the gold standard method for determining RBC lifespans. How-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Levitt’s CO breath test, which has been demonstrated to be not inferior to the [ 15 ] N glycine labelling technique [ 21 ], was applied to detect RBC lifespan. The RBC lifespan was measured as the total capacity of CO from Hb degradation divided by the quantity of CO released per day.…”
Section: Methodsmentioning
confidence: 99%
“…Levitt’s CO breath test, which has been demonstrated to be not inferior to the [ 15 ] N glycine labelling technique [ 21 ], was applied to detect RBC lifespan. The RBC lifespan was measured as the total capacity of CO from Hb degradation divided by the quantity of CO released per day.…”
Section: Methodsmentioning
confidence: 99%
“…RBC lifespan was measured using Levitt's carbon monoxide (CO) breath test by an electrophoretic light scattering (ELS) instrument (Seekya Biotec, Shenzhen, China) as described previously [ 10 ]. RBC lifespan values determined from the CO breath test using this instrument and the 15N-glycine labelling technique have been proved to be comparable, which suggested that the CO breath test is a reliable method for quickly determining human RBC lifespans in clinical applications [ 23 ]. Alveolar air samples were collected pre-dialysis in the morning of the dialysis day without a fasting requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The values of Vb and Vt are approximately the same. Thus, erythrocyte lifespan = (Hb × K)/endPCO [K: 1,380, unit: mL/(dg)] [124][125][126][127]. Hemoglobin concentration can be determined through a routine blood test, while the endogenous CO concentration during expiration can be measured using specific instruments.…”
Section: Co Expiratory Methodsmentioning
confidence: 99%